Current Approaches to Develop a Live Vaccine against Leishmania major - Yeganeh, Farshid; Haji Molla Hoseini, Mostafa (Novelty in Biomedicine, 2017)
Leishmaniasis is an infectious disease that is endemic in 88 countries. Most of the patients after recovery from the infection develop a long-lived natural immunity against re-infection. Reactivation of leishmaniasis subsequent to suppression of the immune system due to HIV infection or administration of systemic immunosuppressive drugs, underscores the importance of developing new drugs and effective vaccine. Despite the many efforts that have been done, there is still no effective vaccine. Up to now, many candidate vaccines from three generations of the vaccine, including Live/killed vaccines, subunit vaccines, and DNA vaccines have been developed and studied. However the sophisticated vaccines, such as prime-boost DNA vaccines are introduced, the best results are obtained from live vaccines. As safety is the most important obstacle to the use of live vaccines, many different approaches have been used to enhance the safety of live vaccine candidates. In this short review, these approaches are summarized.